10u-20=9u-11

Simple and best practice solution for 10u-20=9u-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10u-20=9u-11 equation:


Simplifying
10u + -20 = 9u + -11

Reorder the terms:
-20 + 10u = 9u + -11

Reorder the terms:
-20 + 10u = -11 + 9u

Solving
-20 + 10u = -11 + 9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-9u' to each side of the equation.
-20 + 10u + -9u = -11 + 9u + -9u

Combine like terms: 10u + -9u = 1u
-20 + 1u = -11 + 9u + -9u

Combine like terms: 9u + -9u = 0
-20 + 1u = -11 + 0
-20 + 1u = -11

Add '20' to each side of the equation.
-20 + 20 + 1u = -11 + 20

Combine like terms: -20 + 20 = 0
0 + 1u = -11 + 20
1u = -11 + 20

Combine like terms: -11 + 20 = 9
1u = 9

Divide each side by '1'.
u = 9

Simplifying
u = 9

See similar equations:

| 3(a+2)=a+12 | | 8s^2-30s+18= | | 16m^2-1=15m | | 2x^2-25x+36=0 | | X^2-1x-1=0 | | 6a^2-19a+15= | | -6n+10=-4n-18 | | 7y-10=5y-2 | | -6x-9y=54 | | (9m^3+4n)+7m^3= | | 21-11=5(x-1) | | 8-9x=104-37x | | 6x-2=x-0 | | 6f-14+26-3f-15f= | | -6x+2=1 | | -121-8x=8x+23 | | y^2+3y-16=y-1 | | 3(y-2)=12 | | X^2+19x+K= | | -x=3+2x+16 | | 68=-4(5x+3) | | -10x-106=29-5x | | -21(3t)= | | 28m^2+28m-56=0 | | a+1.6b=8 | | 1.6x-1.2+2.29x=0.28 | | a^2-15a+54=0 | | -102-4x=2x+30 | | -8-3x=8-7x | | 4x+2=7x-12 | | 2.75-0.5t=5-2t | | 8x+5-x=12 |

Equations solver categories